Perceived stigma among people living with HIV AIDS in Pokhara, Nepal - Subedi B; Timilsina BD; Tamrakar N (HIV/AIDS: Research and Palliative Care, 2019)
Babita Subedi,1 Bishow Deep Timilsina,2 Neeta Tamrakar3 1Matrisishu Miteri Hospital, Pokhara, Nepal; 2Surgical Department, Manipal Teaching Hospital, Pokhara, Nepal; 3Tribhuwan University, Institute of Medicine, Pokhara Campus, Pokhara, Nepal Background: HIV-related stigma among people living with HIV/AIDS (PLWHA) is the foremost barrier to HIV prevention, treatment, care, and support. The aim of this study was to identify the perceived stigma level of PLWHA and its relation with selected demographic and situational factors in Pokhara, Nepal.Methods: Cross-sectional descriptive study was conducted among 282 PLWHA after probability sampling from antiretroviral treatment center of Western Regional Hospital, Pokhara, Nepal. Face-to-face interview was taken by using Bunn standard HSS tool. Stigma was measured in terms of felt stigma (public attitude concern [PAC], disclosure concern [DC], negative self-image [NSI]), enacted stigma [ES], as well as overall stigma.Result: The mean score of PAC, DC, NSI, ES, and overall stigma was 3.09, 3.02, 2.79, 1.66, and 2.52, respectively, where mean score of all domains of felt stigma (PAC, DC, and NSI) was >2.5, thus reflecting a higher level of felt stigma. ANOVA and t-test revealed higher level of overall stigma among younger age group (P<0.001), highly educated group (P=0.007), unmarried group (P<0.001), and recently HIV-diagnosed group (P=0.003).Conclusion: The study suggests high level of felt stigma, which has devastating effects on PLWHA as well as leads to nondisclosure of sero-positive status. So considering the significant impact of felt stigma on control of HIV epidemic, it is important to have a broader comprehension of this phenomenon and its repercussions on PLWHA via timely intervention like better educational intervention and counseling to PLWHA, wide-scale societal awareness campaigns, and more focused local interventions. Keywords: stigma, felt stigma, public attitude concern, disclosure concern, negative self-image, enacted stigma, people living with HIV/AIDS